103 Pediatric resident knowledge and comfort in providing care to transgender youth: A single centre needs assessment. (19th August 2020) - Paciocco, Helen; Johnson, Natasha; Hunter, Andrea
Abstract: Background: Transgender youth experience high rates of health disparities and inequities. There is currently no formal curriculum for transgender health within our centre's pediatric residency program. This gap in training is similar to other programs across the country. With the drastic rise in trans youth patients seeking care, general pediatricians will be the first point of contact for many. Pediatricians therefore need to be equipped with the proper knowledge and skill to provide care to these patients. Objectives: We conducted a needs assessment to assess pediatric residents' comfort with the health care needs of transgender patients, and to assess knowledge about the medical management of transgender youth. The goal was to identify learning gaps within our centre's residency program to guide future curriculum. Design/Methods: A survey with Likert scale and case-based questions, based on literature review, identified key components of trans care. The study was granted an exemption from ethics review. Results: We achieved a 50% response rate (24/58) from pediatric residents, and 50% of these residents were in their senior years (PGY3 and PGY4). All residents felt it was important to have trans specific training during residency. While the majority of senior residents received training during their residency, the total duration was estimated to be ≤ 5 hours. Despite the training received, only 50% [95% CI: 30, 70] of residents felt comfortable asking patients about their gender identity, and only 8% [0, 19] and 33% [14, 52] of residents were comfortable diagnosing gender dysphoria in children and teens, respectively. Most residents felt uncomfortable addressing trans specific health care needs, and 83% [62, 100] of senior residents were uncomfortable counselling patients on available gender affirming pharmacologic agents. Similarly, 92% [77, 100] of senior residents felt uncomfortable prescribing either GnRH analogs or hormonal therapy for trans youth. Lastly, only 58% [30, 86] of senior residents felt comfortable performing Tanner staging in trans patients. Conclusion: In order to help narrow the gap in care for trans patients, we need to better educate pediatric residents on trans specific health care. Future curriculum should focus on discussing gender identity, identifying gender dysphoria, performing Tanner staging, and counselling patients on gender affirming pharmacologic therapies. These skills are critical for general pediatricians to adequately provide care to trans youth.